GMR KUAEL : the longest road PPP - Raghuram, G., 1955- (SAGE Knowledge. Cases., 2016)
GMR Infrastructure Limited (GMRIL) had to make a decision on its continued role in the 555.48 km Kishangarh Udaipur Ahmedabad (KUA) Expressway Project, India's then longest road public-private partnership (PPP) project. GMR had terminated the contract citing NHAI's failure in fulfilling Conditions Precedent (CP) of providing (i) environment clearance (EC), (ii) revised toll free notification and (iii) 80% of required land. The case explores concessionaire-authority dynamics in typical Indian infrastructure PPPs. Taking into account its internal strategy, the extant unfavourable investment climate, the Central Government's steps to revive private interest in the highways sector, and NHAI's quick turnaround in fulfilling CP, GMR had to decide how to respond.